Women and morality in Pentecostalism: perspectives on egoism in AFM’s Pretoria church - Nyamugama, Sithembinkosi (Cita konsultindo, 2024)
This article attends to the continued silence over the perspectives of followers on morality which persists particularly concerning women. The insights of women are especially salient given the participation of women in Pentecostal churches as well as the incidents of abuse largely orchestrated by male leaders. Despite the sparse attention afforded to ethics and morality in contemporary Pentecostal practice, moral complexities animate the arena largely drawn from Biblical teachings and church guidance. The paper discusses women’s perceptions of one such moral question via egoism. Egoism has roots in classical Greek philosophy and although dated, continues to serve as a useful framework in which to think about morality. Drawing from the perceptions of women at a Pretoria-based church branch of the Apostolic Faith Mission, the paper suggests that egoism was generally understood as reprehensible. However, away from idealised moral injunctions, egoism is more complexly engaged by the female members, with secrecy forming one mechanism of retaining egoism albeit away from the collegial gaze. The article adds to an empirical gap while setting up a puzzle in the scholarship of how Pentecostals moralize their daily lives.